CRANBERRY, A POTENTIAL ALTERNATIVE TREATMENT FOR URINARY TRACT INFECTIONS - Gjatovska, Liljana Labacevska; Kostovski, Marko; Jurhar-Pavlova, Maja; Kovacheva-Trpkovska, Danica; Jovchevski, Radomir; Mihajlov, Kiril; Grdanoska, Tatjana; Labachevski, Bojan; Pavlovska, Kristina (Journal of Morphological Sciences, 2023)
Vaccinium macrocarpon is perennial plant traditionally used as an herbal medicine in treatment and prevention of UTIs. Although the mechanisms of action are not jet fully understood  it is presumed that they involve interferation with bacterial adhesion and changes in bacterial morphology mainly attributed to the plants proanthocyanidins. Cranberry extracts (CE) standardized for different concentrations of proanthocyanidinnes (PACs), CE in combination with antibiotics (norfloxacin and vancomycin) and antibiotics alone (only antibiotics) were investigated for their effect on different strains of uropathogenic  E.coli, S. saprophyticus  and E. faecalis .  As a source of CE we used commercial herbal supplements containing only Vaccinium macrocarpon extract (37.5 mg PACs) or CE in combination with D-manoza (25, 3 mg PACs). We used bacterial strains isolated  from outpatients with UTIs reffered for routine urine examination at the Institute of microbiology and parasitology. Sensitivity of the pathogens to CE (as monoagent or combined in herbal mix) was evaluated with disc diffusion method. Our results showed stronger effect of CE on the growth of E.coli compared to Gram-positive strains. S. saprophyticus strains were more susceptible to the extract/herbal mixes compared to the enterococci which predominantly presented as recalcitrant to the inhibitory activity of cranberry/herbal mixes. The sample size of this study was small to draw definite conclusions but our results illuminate avenues for future research of the potential of cranberry as an alternative treatment in patients with UTIs. Keywords: cranberry, UTIs, E.coli , antimicrobial resistance